Modified composite LATP solid electrolyte material and preparation method and application thereof
By combining CNTs on the surface of LATP solid electrolyte materials by vapor deposition, the problems of low conductivity and large interface impedance of lithium battery electrode materials are solved, which significantly improves the ionic conductivity and energy density of the battery, and enhances safety and cycle life.
Patent Information
- Application Number
- CN202311387902.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-24
- Publication Date
- 2025-04-25
AI Technical Summary
The existing full/semi/quasi-solid lithium battery electrode materials have low conductivity, high impedance, poor contact between particles, and large interface impedance between electrode active material materials and solid electrolytes, resulting in limited lithium ion transmission.
CNTs are compounded on the surface of LATP by vapor deposition method to form a modified composite LATP solid electrolyte material to improve its electron-conducting and ion-conducting properties.
The ionic conductance and capacity density of electrodes in all-solid-state lithium batteries, semi-solid-state lithium batteries, and quasi-solid-state lithium batteries have been significantly improved, which enhances the safety and energy density of the battery and extends the cycle life.
Smart Images

Figure CN119890421A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium secondary batteries, and in particular to a modified composite LATP solid electrolyte material and a preparation method and application thereof. Background Art
[0002] Power batteries are the core part of new energy vehicles, among which lithium-ion batteries have obvious advantages in cost and energy density, which can greatly improve the economy and convenience of new energy vehicles and dominate the field of power batteries. However, as the market share of new energy vehicles gradually increases, safety incidents caused by power batteries occur from time to time. The root cause is that the current solution-type electrolyte is a flammable organic system with a narrow electrochemical window. These problems cannot be completely solved by conventional improvement methods. Solid electrolytes have a wide electrochemical window and high thermal stability. The introduction of solid electrolytes can not only fundamentally solve the safety problems of lithium-ion batteries, but also greatly simplify the manufacturing and packaging process, and improve the energy density, reliability and design freedom of the battery.
[0003] While introducing solid components as electrode additives into batteries improves safety, there are also some problems, mainly the poor physical contact at the electrolyte / electrode interface. The electrolyte and the electrode maintain point contact, which makes it easy for defects such as cracks and pores to form between the electrolyte and the electrode. The presence of defects limits the transmission of lithium ions at the interface. At the same time, the volume expansion at the interface during the transmission of lithium ions also puts higher requirements on the stability of the solid-solid interface.
[0004] Therefore, how to alleviate or improve the above-mentioned problems by composite processing of solid electrolyte materials and electrode materials is a problem that technicians in this field are constantly exploring. Summary of the invention
[0005] The present invention aims at the problems of low conductivity and high impedance of existing full / semi / quasi-solid-state lithium battery electrode materials, poor contact between particles (including electrical contact), and large interface impedance between electrode active material and solid electrolyte, and proposes a modified composite LATP solid electrolyte material and its preparation method and application, and composites CNTs on the surface of LATP by vapor deposition to obtain a modified composite LATP solid electrolyte material. The method is simple in process, can significantly improve the electronic and ion conductivity of the LATP solid electrolyte, and can effectively improve the ion conductivity and capacity density of the electrodes in full-solid-state lithium batteries, semi-solid-state lithium batteries, and quasi-solid-state lithium batteries.
[0006] To this end, in a first aspect, an embodiment of the present invention provides a method for preparing a modified composite LATP solid electrolyte material, the preparation method comprising:
[0007] Mixing lithium aluminum titanium phosphate (LATP) mixed raw materials and an aqueous solution of a catalyst for gas-phase pyrolysis of CNTs in a mixer, and drying to obtain a mixed material; the LATP mixed raw materials include: a lithium source, an aluminum source, a titanium source, and a phosphorus source;
[0008] The mixed material is sintered in an air atmosphere at a sintering temperature in a sintering furnace for a first period of time, then an inert gas is introduced to remove the air, the temperature is adjusted from the sintering temperature to a catalytic reaction temperature, and then a gaseous carbon source is introduced into the sintering furnace from an air inlet, and the temperature is kept for a second period of time, and then the mixture is cooled to room temperature with the furnace under the protection of an inert atmosphere, and a sample in the sintering furnace is taken out to obtain a LATP material composited with carbon nanotubes CNTs;
[0009] The carbon nanotubes CNTs composite lithium aluminum titanium phosphate LATP material is crushed to obtain the desired modified composite LATP solid electrolyte material.
[0010] Preferably, the catalyst is a mixture of one or more of cobalt nitrate, nickel nitrate, iron nitrate, copper nitrate, aluminum nitrate, manganese nitrate, cobalt sulfate, nickel sulfate, iron sulfate, copper sulfate, aluminum sulfate, manganese sulfate, cobalt chloride, nickel chloride, iron chloride, copper chloride, aluminum chloride, and manganese chloride;
[0011] The mass of the catalyst accounts for 1%-50% of the mass of the LATP mixed raw material;
[0012] The concentration of the aqueous solution of the catalyst is 0.1 mol / L-6.5 mol / L;
[0013] Preferably, the mixing time in the mixer is 0.5h-5h, and the rotation speed of the mixer is 500r / min-5000r / min.
[0014] Preferably, the sintering temperature is 600°C-1200°C, and the sintering time is 4-24h; the catalytic reaction temperature is 500°C-800°C, and the catalytic reaction time is 0.5-2h.
[0015] Preferably, the inert atmosphere is any one of nitrogen, helium and argon.
[0016] Preferably, the gaseous carbon source includes any one of ethane, acetylene, ethylene, methane, carbon monoxide, propane, propyne and propylene.
[0017] Preferably, the speed of introducing the gaseous carbon source is 1 ml / min-100 ml / min, and the total mass of the introduced gaseous carbon source is 1%-50% of the mass of the LATP mixed raw material.
[0018] In a second aspect, an embodiment of the present invention provides a modified composite LATP solid electrolyte material prepared by the preparation method described in the first aspect above.
[0019] In the third aspect, an embodiment of the present invention proposes a use of the modified composite LATP solid electrolyte material described in the second aspect above, wherein the modified composite LATP solid electrolyte material is used for one or more of an electrolyte, a separator, a positive electrode material additive, a negative electrode material additive, and an electrolyte additive.
[0020] In a fourth aspect, an embodiment of the present invention provides a lithium secondary battery, which includes one or more of the electrolyte, separator, positive electrode material additive, negative electrode material additive, and electrolyte additive described in the third aspect.
[0021] The preparation method of the modified composite LATP solid electrolyte material provided in the embodiment of the present invention achieves uniform coating and stable contact of the solid electrolyte LATP by in-situ generation of CNTs through vapor deposition, thereby increasing the electronic conductivity of the solid electrolyte and enabling the material itself to have excellent electronic ion transmission performance. When used as an electrode additive, it can replace the role of electrolyte and conductive additives, reduce the use of electrolyte and conductive additives, improve battery safety and electrochemical window, and improve electrode compaction density and energy density. CNTs are fibrous, which can not only improve electrode density, contact between particles, and contact with active materials; the three-dimensional conductive network structure of CNTs can provide support and stability inside the battery, preventing the active material from detaching from the pole piece when expanding and contracting, which helps to maintain the stability of the battery pole piece, thereby improving the performance and cycle life of the battery. The process of the present invention is simple and has high practicality. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 A flow chart of a method for preparing a modified composite LATP solid electrolyte material provided by an embodiment of the present invention;
[0023] Figure 2 A schematic diagram of a solid electrolyte material of vapor-deposited CNTs composite LATP provided in an embodiment of the present invention;
[0024] Figure 3 A schematic diagram of the enhanced contact between solid electrolyte particles of vapor-deposited CNTs composite LATP provided in an embodiment of the present invention;
[0025] Figure 4 A comparison chart of electrochemical impedance spectra (EIS) of a lithium-ion battery assembled with a solid electrolyte material of vapor-deposited CNTs modified composite LATP provided in Example 2 of the present invention and a conventional LATP solid electrolyte material provided in Comparative Example 1;
[0026] Figure 5 It is a comparison chart of the cycle capacity curves of the lithium-ion battery assembled with the vapor-deposited CNTs modified composite LATP solid electrolyte material provided in Example 2 of the present invention and the traditional LATP solid electrolyte material in Comparative Example 1. DETAILED DESCRIPTION
[0027] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments.
[0028] The present invention provides a method for preparing a modified composite LATP solid electrolyte material, the main steps of which are as follows: Figure 1 As shown, including:
[0029] Step 110, mixing the lithium aluminum titanium phosphate LATP mixed raw material and the aqueous solution of the catalyst for gas phase cracking of CNTs in a mixer, and obtaining a mixed material after drying;
[0030] The LATP mixed raw materials include: lithium source, aluminum source, titanium source, and phosphorus source; wherein the lithium source includes: lithium hydroxide (LiOH), lithium sulfate (Li 2 SO 4 )、Lithium carbonate (Li 2 CO 3 ), lithium chloride (LiCl), etc.; aluminum sources include: aluminum hydroxide (Al(OH) 3 ), aluminum sulfate (Al 2 (SO 4 ) 3 ), aluminum chloride (AlCl 3 ), aluminum hydroxide monohydrate (Al(OH) 3 ·H 2 O), aluminum oxide (Al 2 O 3 ) etc.; Titanium sources include: titanium dioxide (TiO 2 ), titanium chloride (TiCl 4 ) etc.; Phosphorus sources include: phosphoric acid (H 3 PO 4 ), ammonium phosphate (NH 4 ) 3 PO 4 , phosphorus pentoxide (P 2 O 5 )wait.
[0031] The catalyst is a mixture of one or more of cobalt nitrate, nickel nitrate, iron nitrate, copper nitrate, aluminum nitrate, manganese nitrate, cobalt sulfate, nickel sulfate, iron sulfate, copper sulfate, aluminum sulfate, manganese sulfate, cobalt chloride, nickel chloride, iron chloride, copper chloride, aluminum chloride and manganese chloride; the concentration of the aqueous solution of the catalyst is 0.1 mol / L-6.5 mol / L; the mass of the catalyst accounts for 1%-50% of the mass of the LATP mixed raw material.
[0032] Step 120, sintering the mixed material in an air atmosphere at a sintering temperature in a sintering furnace for a first period of time, then introducing an inert gas to remove the air, adjusting the temperature from the sintering temperature to the catalytic reaction temperature, and then introducing a gaseous carbon source into the sintering furnace from the air inlet, keeping the temperature for a second period of time, and then cooling the mixture to room temperature with the furnace under the protection of an inert atmosphere, taking out the sample in the sintering furnace, and obtaining a LATP material composited with carbon nanotubes CNTs;
[0033] Among them, the sintering temperature is 600-1200°C, and the sintering time is 4-24h;
[0034] The catalytic reaction temperature is 500-800°C, the catalytic reaction time is 0.5-2h, and the gaseous carbon source includes any one of ethane, acetylene, ethylene, methane, carbon monoxide, propane, propyne, and propylene. The speed of introducing the gaseous carbon source is 1ml / min-100ml / min, and the total mass of the introduced gaseous carbon source is 1%-50% of the mass of the LATP mixed raw material.
[0035] The inert atmosphere is any one of nitrogen, helium, and argon.
[0036] Step 130, crushing the carbon nanotubes CNTs composite lithium aluminum titanium phosphate LATP material to obtain the desired modified composite LATP solid electrolyte material.
[0037] In the above step 120, the mixture of the LATP mixed raw material and the catalyst is sintered in an air atmosphere, which will lead to the bonding between the raw material particles to form a preliminary LATP basic structure.
[0038] Carbon nanotubes (CNTs) are then introduced into the composite LATP material process by introducing a gas-phase carbon source. The carbon source decomposes at high temperatures to form carbon nanotubes, which are used to modify the material to enhance its electrical conductivity and other properties. Carbon nanotubes are conductive materials, and they can be used as electron conduction paths in batteries, helping to increase the conductivity of electrolyte materials. Carbon nanotubes can also provide a support structure that helps prevent the material from deforming during the battery's charge and discharge process. Therefore, by introducing carbon nanotubes, the performance of the electrolyte material is improved.
[0039] The specific catalytic reaction involves the decomposition and reaction of the carbon source to introduce carbon nanotubes into the LATP material and firmly bind them to the surface of the material through the action of the catalyst. In this process, the catalyst promotes the decomposition of the carbon source and the generation of carbon nanotubes, thereby achieving the modification of the composite LATP material. This modification helps to improve the performance of the electrolyte material.
[0040] The material structure formed by the present invention is as follows Figure 2 , Figure 3 shown.
[0041] Figure 2 Schematic diagram of a solid electrolyte material of vapor-deposited CNTs composite LATP provided in an embodiment of the present invention; the fibrous substance in the figure is carbon nanotubes CNTs, the large round spheres are LATP solid electrolyte particles, and the small round spheres on the surface of the LATP solid electrolyte particles are the binding sites of the catalyst for vapor-phase decomposition of CNTs.
[0042] Figure 3 This is a schematic diagram of the enhanced contact between solid electrolyte particles of vapor-deposited CNTs composite LATP. It can be seen that the fibrous nature of CNTs can not only improve the electrode density, the contact between particles, and the contact with active materials, but the three-dimensional conductive network structure of CNTs can also provide support and improve stability inside the battery.
[0043] The process of the present invention is simple and has high practicality. The prepared modified composite LATP solid electrolyte material can be used for one or more of electrolyte, separator, positive electrode material additive, negative electrode material additive and electrolyte additive, and is applied in lithium secondary batteries.
[0044] In order to more clearly illustrate the purpose and advantages of the present invention, the present invention is further described below in conjunction with the embodiments. In addition, the embodiments described in the present invention are only partial embodiments. Based on the embodiments described in the present invention, all other embodiments obtained by those skilled in the art without creative work are within the protection scope of the present invention. In addition, it should be understood that these embodiments are only used for more detailed description and should not be understood as limiting the present invention in any form, that is, they are not intended to limit the protection scope of the present invention.
[0045] Example 1
[0046] Example 1 of the present invention provides a specific preparation process and performance of a solid electrolyte material of a vapor-deposited CNTs-modified composite LATP.
[0047] The LATP mixed raw materials of lithium carbonate, aluminum oxide, titanium dioxide, phosphorus pentoxide in a mass ratio of 2:1:4.5:8 and the aqueous solution of cobalt nitrate catalyst for gas phase cracking CNTs are fully mixed in a mixer, the mixing time is 2 hours, and the speed of the mixer is 2500r / min; the mass of the added aqueous solution of cobalt nitrate catalyst accounts for 10% of the mass of the LATP mixed raw materials, and the concentration of the aqueous solution of the catalyst is 1mol / L. Drying is performed after mixing.
[0048] The temperature was raised to 900°C at a rate of 5°C / min, and the mixed material was sintered in an air atmosphere. The temperature was kept for 4 hours, and then inert gas argon was introduced to remove the air. The temperature was adjusted to 800°C, the catalytic reaction temperature, and the temperature was kept for 1 hour. The gas phase carbon source C 2 H 2 The gas phase carbon source was introduced into the sintering furnace at a speed of 10 ml / min. The total mass of the gas phase carbon source introduced was 5% of the mass of the LATP mixed raw material. When the reaction was completed, the heating was stopped and the temperature was naturally cooled to room temperature.
[0049] The obtained material is crushed to obtain the desired vapor-deposited CNTs-modified composite LATP solid electrolyte material.
[0050] The electrochemical impedance spectroscopy (EIS) diagram of the solid electrolyte material of the vapor-deposited CNTs modified composite LATP is shown in FIG. Figure 4 shown.
[0051] The assembled lithium-ion battery was subjected to a cycle capacity test, and the battery assembly method and test conditions were as follows: the solid electrolyte material of vapor-deposited CNTs composite LATP prepared in this embodiment was used as a positive electrode additive in an amount of 2% of the positive electrode mass, and the lithium-ion battery was assembled by a conventional method, wherein lithium cobalt oxide was used as the positive electrode and lithium metal was used as the negative electrode; the test conditions were: charge and discharge current 0.1A / g, charge cut-off voltage 4.2V, and discharge cut-off voltage 2V.
[0052] Example 2
[0053] Example 2 of the present invention provides a specific preparation process and performance of a solid electrolyte material of a vapor-deposited CNTs-modified composite LATP.
[0054] The LATP mixed raw materials of lithium hydroxide, aluminum hydroxide monohydrate, titanium dioxide, and ammonium phosphate in a mass ratio of 4:1:4.5:4.5 and the aqueous solution of copper sulfate, a catalyst for gas phase cracking of CNTs, are fully mixed in a mixer for 2 hours at a mixer speed of 3000 r / min; the mass of the copper sulfate aqueous solution of the added catalyst accounts for 20% of the mass of the LATP mixed raw materials, and the concentration of the catalyst aqueous solution is 1 mol / L. Drying is performed after mixing.
[0055] The temperature was raised to 900°C at a rate of 3°C / min, and the mixed material was sintered in an air atmosphere. The temperature was kept at this temperature for 5 hours, and then the inert gas argon was introduced to remove the air. The temperature was adjusted to the catalytic reaction temperature of 750°C and kept at this temperature for 1 hour. The gas phase carbon source C 3 H 6 The gas phase carbon source was introduced into the sintering furnace at a speed of 20 ml / min. The total mass of the gas phase carbon source introduced was 10% of the mass of the LATP mixed raw material. When the reaction was completed, the heating was stopped and the temperature was naturally cooled to room temperature.
[0056] The obtained material is crushed to obtain the desired vapor-deposited CNTs-modified composite LATP solid electrolyte material.
[0057] Comparative Example 1
[0058] Comparative Example 1 of the present invention provides a specific preparation process and performance of a solid electrolyte material of LATP.
[0059] The LATP mixed raw materials of lithium carbonate, aluminum oxide, titanium dioxide and phosphorus pentoxide in a mass ratio of 2:1:4.5:8 are fully mixed in a mixer. The mixing time is 2 hours. The speed of the mixer is 2500r / min. Drying is performed after mixing.
[0060] The temperature was raised to 900°C at 5°C / min, and the mixed material was sintered in an air atmosphere and kept at this temperature for 4 hours. The obtained material was crushed to obtain the desired LATP solid electrolyte material.
[0061] The test method is the same as in Example 1.
[0062] pass Figure 4 As shown, it can be seen that the impedance of Example 1 is smaller than that of Comparative Example 1, indicating that compared with the LATP without CNTs composite in Comparative Example 1, the solid electrolyte material of the vapor-deposited CNTs-modified composite LATP prepared in Example 1 can greatly reduce the interfacial impedance in the electrochemical reaction of the battery, thereby inhibiting the occurrence of interfacial side reactions and achieving a more stable long cycle.
[0063] pass Figure 5 As shown, it can be seen that the lithium-ion battery cycle of the solid electrolyte material containing vapor-deposited CNTs modified composite LATP is relatively stable.
[0064] The preparation method of the modified composite LATP solid electrolyte material provided in the embodiment of the present invention achieves uniform coating and stable contact of the solid electrolyte LATP by in-situ generation of CNTs through vapor deposition, thereby increasing the electronic conductivity of the solid electrolyte and enabling the material itself to have excellent electronic ion transmission performance. When used as an electrode additive, it can replace the role of electrolyte and conductive additives, reduce the use of electrolyte and conductive additives, improve battery safety and electrochemical window, and improve electrode compaction density and energy density. CNTs are fibrous, which can not only improve electrode density, contact between particles, and contact with active materials; the three-dimensional conductive network structure of CNTs can provide support and stability inside the battery, preventing the active material from detaching from the pole piece when expanding and contracting, which helps to maintain the stability of the battery pole piece, thereby improving the performance and cycle life of the battery. The process of the present invention is simple and has high practicality.
[0065] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A method for preparing a modified composite LATP solid electrolyte material, characterized in that: The preparation method comprises: A lithium aluminum titanium phosphate (LATP) mixed raw material and an aqueous solution of a catalyst for gas phase cracking of CNTs are mixed in a mixer, and dried to obtain a mixed material; the LATP mixed raw material comprises: a lithium source, an aluminum source, a titanium source, and a phosphorus source; The mixed material is sintered in an air atmosphere at a sintering temperature in a sintering furnace for a first period of time, then an inert gas is introduced to remove the air, the temperature is adjusted from the sintering temperature to a catalytic reaction temperature, and then a gaseous carbon source is introduced into the sintering furnace from an air inlet, and the temperature is kept for a second period of time, and then the mixture is cooled to room temperature with the furnace under the protection of an inert atmosphere, and a sample in the sintering furnace is taken out to obtain a LATP material composited with carbon nanotubes CNTs; The carbon nanotubes CNTs composite lithium aluminum titanium phosphate LATP material is crushed to obtain the desired modified composite LATP solid electrolyte material.
2. The method for preparing the modified composite LATP solid electrolyte material according to claim 1, characterized in that: The catalyst is a mixture of one or more of cobalt nitrate, nickel nitrate, iron nitrate, copper nitrate, aluminum nitrate, manganese nitrate, cobalt sulfate, nickel sulfate, iron sulfate, copper sulfate, aluminum sulfate, manganese sulfate, cobalt chloride, nickel chloride, iron chloride, copper chloride, aluminum chloride, and manganese chloride; The mass of the catalyst accounts for 1%-50% of the mass of the LATP mixed raw material; The concentration of the aqueous solution of the catalyst is 0.1 mol / L-6.5 mol / L.
3. The method for preparing the modified composite LATP solid electrolyte material according to claim 1, characterized in that: The mixing time in the mixer is 0.5h-5h, and the rotating speed of the mixer is 500r / min-5000r / min.
4. The method for preparing the modified composite LATP solid electrolyte material according to claim 1, characterized in that: The sintering temperature is 600-1200° C., and the sintering time is 4-24 hours; the catalytic reaction temperature is 500-800° C., and the catalytic reaction time is 0.5-2 hours.
5. The method for preparing the modified composite LATP solid electrolyte material according to claim 1, characterized in that: The inert atmosphere is any one of nitrogen, helium and argon.
6. The method for preparing the modified composite LATP solid electrolyte material according to claim 1, characterized in that: The gas phase carbon source includes any one of ethane, acetylene, ethylene, methane, carbon monoxide, propane, propyne and propylene.
7. The method for preparing the modified composite LATP solid electrolyte material according to claim 1, characterized in that: The speed of introducing the gas phase carbon source is 1 ml / min-100 ml / min, and the total mass of the introduced gas phase carbon source is 1%-50% of the mass of the LATP mixed raw material.
8. A modified composite LATP solid electrolyte material prepared according to the method of any one of claims 1-7.
9. A use of the modified composite LATP solid electrolyte material according to claim 8, characterized in that: The modified composite LATP solid electrolyte material is used for one or more of an electrolyte, a separator, a positive electrode material additive, a negative electrode material additive, and an electrolyte additive.
10. A lithium secondary battery, characterized in that: The lithium secondary battery comprises one or more of the electrolyte, separator, positive electrode material additive, negative electrode material additive, and electrolyte additive as described in claim 9 above.